The Effect of Eating Food Patterns with Nutritional Status of Age 12 - 24 Months in The Working Area of Pademawu Pademawu District, Pademawu District, Pamekasan District - Maksum, Ali; Mindiharto, S.PSi., M.Kes, sestiono (Journal of Public Health Science Research (JPHSR), 2020)
Malnutrition is a malnourishment condition resulting from the imbalance of micro nutrient an macro nutrien. Parental diet can help create problems related to the nutritional status of toddlers. Giving the child a right opportunity to consume food does not assure the toddler to be free of his nutritional statis. That’s why researches are interested in studying the effectof a diet for twelfth-twenty fourth months old of child’snutritional status. The sample design of this study is taken for sixty nine respondents, data gathering on the foster diet variabel diet question naire and variable data nutritional status with anthropo metric mesures. The collected data was analyzed using cross table analysis. Cross table analysis showsthat there is a linkbetween the foster diet and thet welfth-twenty fourth months old of child’s nutritional status, and the diet of democratic food has the highest impact on the nutritional status of the toodler twelfth-twenty fourth months old of child’s nutritional status at the medical center of Pademawu, Pamekasan. The study found that there is a nurturing pattern of eating under the child’s twelfth-twenty fourth months old of child’s nutritional status by the most dominan foster pattern is the democratic upbringing in the workplace of the medical center of Pademawu, Pamekasan.